Virulence Determinants Are Required for Brain Abscess Formation Through Staphylococcus aureus Infection and Are Potential Targets of Antivirulence Factor Therapy - Zheng, Ying; Shang, Weilong; Peng, Huagang; Rao, Yifan; Zhao, Xia; Hu, Zhen; Yang, Yi; Hu, Qiwen; Tan, Li; Xiong, Kun; Li, Shu; Zhu, Junmin; et al. (Frontiers in Microbiology, 2019)
Bacterial brain abscesses (BAs) are difﬁcult to treat with conventional antibiotics. Thus, the development of alternative therapeutic strategies for BAs is of high priority. Identifying the virulence determinants that contribute to BA formation induced by Staphylococcus aureus would improve the effectiveness of interventions for this disease. In this study, RT-qPCR was performed to compare the expression levels of 42 putative virulence determinants of S. aureus strains Newman and XQ during BA formation, murine ear colonization, and bacteremia. The alterations in the expression levels of 23 genes were further confirmed through specific TaqMan RT-qPCR. Eleven S. aureus genes that persistently upregulated expression levels during BA infection were identified, and their functions in BA formation were confirmed through isogenic mutant experiments. Bacterial loads and BA volumes in mice infected with isdA, isdC, lgt, hla, or spa deletion mutants and the hla/spa double mutant strain were lower than those in mice infected with the wild-type Newman strain. The therapeutic application of monoclonal antibodies against Hla and SpA decreased bacterial loads and BA volume in mice infected with Newman. This study provides insights into the virulence determinants that contribute to staphylococcal BA formation and a paradigm for antivirulence factor therapy against S. aureus infections.